Evaluating Eye Injuries from Traffic Accidents in Turkey: American Medical Association Guideline vs. National Regulations - Turan, Abdullah; Gamsız Bilgin, Nursel; Kar, Hakan (The Bulletin of Legal Medicine, 2024)
Objective: Traffic accidents are increasingly responsible for eye injuries, especially in developing countries. Through the analysis of impairment rates, this research aims to identify the strengths and weaknesses of the impairment assessment criteria. Methods: Patients who applied to between January 1, 2015, and January 1, 2022 with eye injuries connected to traffic accidents had their sociodemographic and accident-related data scanned. Impairment rates were calculated individually for each case in accordance with the American Medical Association Guides to the Evaluation of Permanent Impairment (AMA guideline), the Regulation on Disability Assessment for Adults (Disability regulation), and The Regulation on Determination of Working Power and Loss of Profitability in Occupations [Social Security Institution (SSI) regulation]. Results: In our study, 67.1% of the 82 cases were male, with a mean age of 36.01. The cases exhibited the most common occurrences of corneal and nerve injuries. We observed a statistically significant difference in the medians of impairment rates calculated according to the AMA guidelines and the Disability and SSI regulations. Conclusion: The calculation of impairment rates based on the SSI regulation for eye injuries revealed a constrained methodology, resulting in higher impairment rates compared to those determined by the AMA guideline and the Disability regulation. The Disability regulation and AMA guidelines were found to follow similar and detailed calculation methodologies. Within our country, we advocate for the adoption of a comprehensive guideline devoid of subjective interpretation for the determination of impairment rates in eye injuries resulting from traffic accidents, encompassing all conceivable eye-related diagnoses.